1994
DOI: 10.1002/jez.1402690303
|View full text |Cite
|
Sign up to set email alerts
|

Effects of extracellular matrix proteins on macrophage differentiation, growth, and function: Comparison of liquid and agar culture systems

Abstract: Both spaceflight and skeletal unloading suppress the haematopoietic differentiation of macrophages (Sonnenfeld et al., Aviat. Space Environ. Med., 61:648-653, 1990; Armstrong et al., J. Appl. Physiol., 75:2734-2739, 1993). The mechanism behind this reduction in haematopoiesis has yet to be elucidated. However, changes in bone marrow extracellular matrix (ECM) may be involved. To further understand the role of ECM products in macrophage differentiation, we have performed experiments evaluating the effects of fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

1994
1994
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…This is in agreement with the evidence, in several tissues, of the role of extracellular matrix components (fibronectin, laminin, type I and IV collagens, etc.) in modulating in situ the processes of macrophagic differentiation and activation [37,38]. Our findings indicated that, between the two types of collagen, the higher effects on cytodifferentiation and activation are observed in the presence of type I collagen with respect to type IV collagen.…”
Section: Discussionmentioning
confidence: 71%
“…This is in agreement with the evidence, in several tissues, of the role of extracellular matrix components (fibronectin, laminin, type I and IV collagens, etc.) in modulating in situ the processes of macrophagic differentiation and activation [37,38]. Our findings indicated that, between the two types of collagen, the higher effects on cytodifferentiation and activation are observed in the presence of type I collagen with respect to type IV collagen.…”
Section: Discussionmentioning
confidence: 71%
“…Although ECM coatings on two‐dimensional (2D) culture surfaces provide some insight to the effect of composition on macrophage function, it poorly recapitulates the three‐dimensional (3D) environment that cells experience in the body. In the same early study described above, BMDMs were cultured in agar suspensions containing ECM proteins, IL‐6 secretion was significantly reduced compared to control agar with no ECM protein, suggesting that adhesion to the matrix in a 3D environment modulates macrophage cytokine secretion. Our laboratory observed that macrophages cultured on top of fibrin gels generated by polymerization of fibrinogen using thrombin, exhibit reduced secretion of TNFα when compared to cells cultured on polystyrene surfaces .…”
Section: Regulation Of Macrophages By Biophysical Cuesmentioning
confidence: 83%
“…To investigate the effects of ECM composition on macrophages, cells can be cultured on surfaces coated with various ECM proteins, and their behavior examined. In an early study, bone marrow‐derived macrophages (BMDMs) cultured on dishes coated with fibronectin, laminin, type I collagen or type IV collagen were found to have a slower growth rate when compared to cells cultured on tissue culture plastic alone, which naturally adsorbs soluble ECM proteins found in serum . Cells adopted different morphologies on different ECMs, with collagen IV and laminin causing a rounder shape, compared to the other ECMs.…”
Section: Regulation Of Macrophages By Biophysical Cuesmentioning
confidence: 99%
See 1 more Smart Citation
“…It was reported that ECM also plays a role in the differentiation of embryonic stem cells [35] and skeletal muscle cells [36] . Armstrong et al [37] have shown that ECM proteins have effects on MAC differentiation, growth and function.…”
Section: Discussionmentioning
confidence: 99%